GOOD CITIZEN: THE RESPONSIBILITY OF TEACHERS TO SHAPE THE CHARACTER OF MAN 1 SAMARINDA STUDENTS DURING THE COVID-19 PANDEMIC - Suryaningsi; Aldo Aditya Ramadhan (Bajang Institute, 2021)
This research focuses on the responsibility of PPKn teachers in carrying out their obligations as a professional, guru PPKn is considered to have a very heavy responsibility to the entire community to grow, shape, maintain morals and exist in accordance with Pancasila in the body of the nation's generation. The purpose of this study is to investigate the efforts of VAT Teachers in forming Good Citizen in MAN 1 Samarinda students, whocan form students whoexcel, excel, and at the same time become good citizens. This research uses a type of qualitative deriftive research. Primary data sources from guru and MAN 1 Samarinda students. Data collection techniques use observations, interviews, and documentation. Secondary data sources are obtained from schools with soft files or hard files. Data analysis techniques use miles and huberman models i.e. data collection, data reduction and conclusion withdrawal. The validity of data uses triangulation of data sources. The results of research on upaya conducted by PPKn teachers to attract students, by providing assignments to display skills in the classroom and extra activities of development ofskills outside the classroom. Ppkn MAN 1 Samarinda teachers have made maximum efforts to attract students to PPKn lessons by providing extra learning activities outside the classroom with a variety of activity options but there are still some students who are unable or reluctant to participate in these activities so that the formation of Good Citizen MAN 1 Samarinda becomes hampered. This research can be tested in high school